Adolescents’ psychological well-being after parental divorce in Indonesia: an interpretative phenomenological analysis - Slametiningsih Slametiningsih; Achir Yani S. Hamid; Imami Nur Rachmah; Mustikasari Mustikasari; Raden Irawati Ismail (International Journal of Public Health Science (IJPHS), 2026)
Parental divorce has increased in Indonesia and may adversely affect adolescents’ psychological well-being. However, limited qualitative research has explored how adolescents interpret divorce within the Indonesian sociocultural context. This study aimed to explore adolescents’ experiences of psychological well-being following parental divorce and identify coping processes that foster resilience. A qualitative study using an interpretative phenomenological analysis (IPA) approach was conducted. Semi-structured interviews were carried out with five female adolescents aged 14-15 years who had experienced parental divorce. Participants were purposively recruited from a junior high school in Bekasi, Indonesia. Data were analyzed using IPA to examine lived experiences and meaning-making processes. Three themes emerged: i) self-acceptance and identity reconstruction, ii) relational ecosystems as double-edged support systems, and iii) transition from survival strategies to purposeful autonomy. Participants described grief, self-blame, academic disruption, and social stigma. However, supportive relationships with peers, extended family, and teachers promoted adaptive coping and resilience. These findings highlight that parental divorce affects adolescent psychological well-being, but supportive environments can mitigate negative outcomes. School-based mental health programs, anti-stigma initiatives, and culturally sensitive counseling services are recommended to support adolescents experiencing family transitions.